Questioning Joko Widodo’s Global Maritime Fulcrum: Change and Overlap Policy (Department of International Relations, Universitas Brawijaya, 2021)
The Global Maritime Fulcrum is a strategy chosen by President Joko Widodo (Jokowi), declared in 2014, consisting of 7 pillars. This program has been running for three years since Presidential Regulation Number 16 of 2017 concerning the Indonesian Maritime Policy mainly focuses on domestic pillars such as the Sea Highway. This policy did not last long when President Jokowi entered his second term to focus on the vision of Indonesia Maju, which emphasized Indonesia's position as a developing country. Using Rumelt's right strategic approach and bad strategy and changes and continuity in foreign policy, the author tries to find the extent to which the implementation of Indonesian Marine policy can become Indonesia's central foreign policy? This research found, among other things: 1) Indonesian Marine Policy authorities overlap, even though there is no clear multi-sectoral scope of work between agencies. 2) The focus on domestic needs only makes the Indonesian Maritime Policy rely on the Sea Highway as the primary focus so that it is not oriented towards an outward-looking and long-term vision. 3) The lack of commitment of President Jokowi's administration in executing the points in the Presidential Regulation. The study concludes that President Jokowi completely changed Indonesia's Maritime Policy strategy in his second term.